PENGEMBANGAN BAHAN AJAR MENULIS TEKS EKSPLANASI DENGAN PENDEKATAN KOOPERATIF MODEL STAD KELAS XI SMK NEGERI 6 SAMARINDA - NFN Alimah (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2018)
This research aims to determine the design of teaching materials and to know the implementation and effectiveness in the learning of explanation text writing. It uses the development of teaching materials and cooperative learning strategy (STAD) on 11th grade students of SMK Negeri 6 Samarinda. It is a research and development. This study brings about teaching material products proved by validator teams and education practitioners. The data analysis shows that STAD can improve the average of students’ learning outcomes and percentage of students’ mastery learning. The average is 67.93 on the first experiment of big group and 92,57 on the second experiment.